Attitudes of University Students towards Indo-Costa Rican Languages - Marín Esquivel, Rebeca (2022)
This article presents a quantitative analysis of the attitudes towards the indigenous languages of Costa Rica by Spanish-speaking Costa Rican university students. To date, little was known about the attitude of non-indigenous students and native speakers of Spanish toward indigenous linguistic heritage and toward the possibility of learning about these languages to enrich their academic and cultural knowledge.